Analisis Pemberian Kredit Pemilikan Rumah (KPR) Dalam Rangka Mengurangi Non Performing Loan (Studi Kasus PT. Bank Tabungan Negara Tbk. Cabang Bogor) - Vina Islami; vina islami (Universitas Bina Sarana Informatika, 2019)
AbstractThe purpose of this study to determine: (1) on the system mortgage (mortgage) PT. Bank Bank Tabungan Negara Tbk. Bogor Branch, (2) analyze the effectiveness of the system of mortgage (mortgage) in order to reduce non-performing loans. This type of research is a descriptive study. Studies using primary data sources and secondary data sources, with the data from interviews with employees. Data collection techniques using observation, interviews, and documentation. The results of the research showed that the system of credit is good enough to see the results of the NPL, but still lack a document - a document that is used to clarify the penginformasian system of mortgage (mortgage). And there is a discrepancy of employees in the implementation of tasks and responsibilities. Keyword : System, Housing Loan, Non-performing loan, the Internal Control